2014
DOI: 10.9790/0853-131035357
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological Evaluation of Postmenopausal Bleeding

Abstract: Post menopausal bleeding is generally regarded as an ominous and serious alarm of genital pathologies. The term "post menopausal bleeding" generally implies bleeding from the uterus and it is essentially the only bleeding of importance at the postmenopausal age. However in the practical sense the term also includes some instances of bleeding from the vagina, urethra or vulva, in which case a uterine source is held suspect until excluded. Being a symptom of varied etiologies and its strong association with mali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
9
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 11 publications
6
9
1
Order By: Relevance
“…Karmarkar et al studying PMB found 87.2% cases in 41-60 age group and rest above 60. 9 Adenomyosis was most commonly seen in the 41-50 age group (50.5%) followed by the thirties(44.1%), and 95% of leiomyomas as well as polyps were in the 30-50 age group [ Table 9] which are comparable to that of Rizvi et al 4 61% of benign endometrial hyperplasias were in the 30-40 age group while 66.7% of endometrial adenocarcinoma were in the 41-50 age group.…”
Section: Discussionsupporting
confidence: 61%
“…Karmarkar et al studying PMB found 87.2% cases in 41-60 age group and rest above 60. 9 Adenomyosis was most commonly seen in the 41-50 age group (50.5%) followed by the thirties(44.1%), and 95% of leiomyomas as well as polyps were in the 30-50 age group [ Table 9] which are comparable to that of Rizvi et al 4 61% of benign endometrial hyperplasias were in the 30-40 age group while 66.7% of endometrial adenocarcinoma were in the 41-50 age group.…”
Section: Discussionsupporting
confidence: 61%
“…9 It does not require hospitalisation, antibiotics and are more diagnostic enabling simultaneous endometrial biopsy for histopathology. 10 Though genital malignancies attribute to 10% of postmenopausal bleeding, high degree of suspicion is to be raised as early diagnosis and management of cancers have high cure and survival rate. 11 A community based cross sectional study conducted by Aswathy et al in rural Kerala and a hospital based study by Kumar in Mangalore reported a low screening rate of 6.9% and 7.2% respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Pragati et al observed a similar finding of 32.5% of functional endometrium in his study for which the women required long term follow up. 18 Endometrial hyperplasia was found in 5 to 10% of cases of postmenopausal bleeding mainly due to hyperestrogenism due to either obesity, exogenous estrogens or estrogen secreting ovarian tumour. Clinically significant hyperplasia evolves with a background of functional endometrium due to protracted exposure to estrogens in the absence of progesterone, an established factor for endometrial cancer.…”
Section: Resultsmentioning
confidence: 99%
“…The patient requires no systemic sedatives or medications as the procedure is usual painlessly, no injury to vaginal outlet. 8,9 Women with PMB has a 10% risk of having genital malignancies such as cervical cancer, endometrial cancer, vaginal, ovarian, and vulval cancers along with a 10% risk of significant pathology 10 . Although PMB is often associated with benign pathologies, the possibility of having an underlying malignancy makes it a sinister complaint requiring thorough clinical work up.…”
Section: Resultsmentioning
confidence: 99%